Analysis of the Hydrocarbon Sector in Bolivia: How are the Gas and Oil Revenues Distributed? - Christian Velasquez-Donaldson (Institute for Advanced Development Studies (INESAD), 2007)
This report analyzes the importance of the hydrocarbon sector in Bolivia. The oil and gas sector currently represents a vital component of the Bolivian economy, accounting for 7 percent of the GDP in term of production and more than 30 percent of total government income. In addition, the hydrocarbon sector not only represents an important economic sector but also a political and social instrument for negotiations, mobilization and social participation. The hydrocarbon sector in Bolivia also plays a strategic geopolitical role in South America as it has the second largest reserves of natural gas in the region after Venezuela. However, the current Bolivian nationalization process has placed this privileged position of the country into question as Bolivia is trying to undo twenty years of neo-liberal policies with the adoption of more nationalistic policies, assuming the control of the sector and challenging the international community and the private sector to benefit its population. The report also exposes that the important hydrocarbon revenues are not evenly distributed across the country s regions. The most important instruments of taxation, royalties and the IDH, are creating a disequilibrium implying that regions with large populations get considerably fewer resources than less populated regions. In addition, the current distribution system, which is based on political criteria with some regional notion of fairness, is discriminatory in the allocation of resources with out taking into account poverty criteria. In a poor country like Bolivia with a strong political framework on poverty alleviation, the lack of poverty criteria in the distribution system of such significant resources makes 1.5 million poor people from La Paz get fewer resources than 300 thousand poor people from Pando in terms of per capita distribution (16 dollars per capita in La Paz vs. 600 dollars per capita in Pando). The report has found that the distribution system of the hydrocarbon revenues needs serious changes to be more efficient and accomplish the goal of poverty reduction. The current system of revenue allocation creates significant per capita inequalities between regions and exacerbates the regional dependency on central transfers that depends on exhaustible and unstable hydrocarbon production (92 percent of the prefecturas revenues and 66 percent of the municipalities revenues come from government transfers). In addition, the decentralization process of the country has several weaknesses. It does not allow local governments to create their own tributary policies and generate their own resources, with exception of municipalities that to some extent can administrate and collect two regional taxes defined by the central government. This disequilibrium has the potential to seriously threaten the unity of the country as a nation. This situation will encourage producing regions to push for a large degree of decentralization in order to take advantage of the enormous inflows of resources that the sector is generating. In addition, non-producing regions will push for a significant share of those large resources given the severe degree of poverty in the country. This leads to two important questions to ask; first, who owns the natural resources, producing regions or the central government, and second, how those revenues should be distributed? 3 In general, those questions are hard to answer and in most cases the answers have significant political notions. In this aspect, the report presents results of a hypothetical calculation in which we combine to some extent the notion that producing regions have the right to a share of the revenues as does the central government. Because producing regions have solid arguments to claim ownership, like natural heritage and social cost reimbursement, we found undesirable and unviable the idea of completely draining those resources from them. Nonetheless, the central government also has significant arguments to have a share of those revenues, like income stability, fiscal equilibrium and macroeconomic considerations. Therefore, we found it important that the central government should benefit from a share of the natural wealth. However, the results of the hypothetical exercise presented in this report have the objective of opening the debate and dialogue for needed changes in the Bolivian hydrocarbon distribution system rather than suggesting a definitive answer for a distribution system in Bolivia.
Keywords: E62; D63; Q34; Q38; 330; Hydrocarbons; Tributary System; Resources Allocation; Transfer System; Bolivia